Angel : a Maximum Ride thriller - Patterson, James, 1947- (Arrow, 2011)
Heartbroken after her best friend and soul mate, Fang, leaves her flock, Maximum Ride begins to believe the evil scientists trying to convince her she needs to save the world, and that Dylan, the newest member of her flock, is her perfect mate.